1998
DOI: 10.1016/s0008-6363(97)00202-2
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to oxidized low-density lipoprotein in vivo enhances intimal thickening and selectively impairs endothelium-dependent dilation in the rabbit

Abstract: Our results show for the first time that local vascular exposure to oxLDL in vivo promotes intimal thickening and inhibits endothelium-dependent dilation, thereby supporting an active role for oxLDL in the morphological and functional changes observed in atherosclerotic blood vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…On the other hand, galactose-induced deficits in relaxation of aortas were prevented by aldose reductase inhibition [21]. Moreover, polyol accumulation and osmotic stress lead to compromised integrity of cell membranes [36], which facilitates non-receptor-mediated uptake of oxidized low-density lipoproteins which are implicated in intimal thickening [37,38]. Our study also morphologically confirmed that the intimal thickening of coronary arteries of galactosaemic dogs can be prevented by an aldose reductase inhibitor.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, galactose-induced deficits in relaxation of aortas were prevented by aldose reductase inhibition [21]. Moreover, polyol accumulation and osmotic stress lead to compromised integrity of cell membranes [36], which facilitates non-receptor-mediated uptake of oxidized low-density lipoproteins which are implicated in intimal thickening [37,38]. Our study also morphologically confirmed that the intimal thickening of coronary arteries of galactosaemic dogs can be prevented by an aldose reductase inhibitor.…”
Section: Discussionsupporting
confidence: 78%
“…LDL has been reported to inhibit the ability of blood vessels to relax [34], to induce a further contraction in vessels pretreated with contractile agonists [35], and to make vessels more prone to vasospasm in response to contractile stimuli [36]. However, no contraction-inducing agonists were used in this study, and no apparent contraction was observed upon addition of LDL.…”
Section: Discussionmentioning
confidence: 87%
“…OxLDL is toxic to endothelial cells [14]and causes the production of superoxide anions by endothelial cells [15], an effect which may augment or accelerate endothelial dysfunction [16, 17, 18]. Furthermore, blood vessels exposed to OxLDL following injury show enhanced intimal thickening [19], confirming a role for OxLDL in the long-term sequelae of vascular injury. Endothelial cells are capable of internalizing minimally oxidized LDL (mmLDL), which corresponds to a physiological level of LDL oxidation.…”
Section: Introductionmentioning
confidence: 99%